2019
DOI: 10.1007/s12975-019-00773-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Organoids Repair Ischemic Stroke Brain Injury

Abstract: Stroke is the second leading cause of death and main cause of disability worldwide, but with few effective therapies. Although stem cell-based therapy has been proposed as an exciting regenerative medicine strategy for brain injury, there are limitations. The developed cerebral organoids (COs) represent a promising transplantation source for stroke that remains to be answered. Here, we transplanted COs at 55 days and explored the feasibility in the rat middle cerebral artery occlusion (MCAO) model of stroke. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 44 publications
0
54
0
Order By: Relevance
“…Organoids were transplanted at 55 days in the rat middle cerebral artery occlusion, and results, 6 h–24 h later, demonstrated that cerebral organoids were able to differentiate and migrate into different brain regions. Also, they observed reduced brain damage volume, synaptic reconstruction, and neurological motor function recovery, among other neurological improvements, likely due to cell survival and vascularization, cell multilineage differentiation, and cellular replacement after stroke [ 65 ].…”
Section: Transplantation Of Organoidsmentioning
confidence: 99%
“…Organoids were transplanted at 55 days in the rat middle cerebral artery occlusion, and results, 6 h–24 h later, demonstrated that cerebral organoids were able to differentiate and migrate into different brain regions. Also, they observed reduced brain damage volume, synaptic reconstruction, and neurological motor function recovery, among other neurological improvements, likely due to cell survival and vascularization, cell multilineage differentiation, and cellular replacement after stroke [ 65 ].…”
Section: Transplantation Of Organoidsmentioning
confidence: 99%
“…Today, they are the closest in vitro model of the human brain. They have assisted in the understanding of several neurological diseases: those of embryonic origin such as autism [ 42 , 56 , 57 ], genetic or viral-induced microencephaly [ 30 , 35 , 58 ], lissencephaly and Miller-Dieker syndrome [ 59 , 60 ], but also those of the aging brain such as Parkinson’s disease [ 61 63 ], Alzheimer’s disease [ 64 ], stroke [ 65 , 66 ] and brain tumors such as glioblastomas [ 67 69 ]. They are also expected to be more predictive for drug development.…”
Section: Biological Issues Addressed By Cerebral Organoidsmentioning
confidence: 99%
“…Therefore, brain organoids are expected to be plausible cell sources for transplantation. A study by Wang et al exploring the effects of brain organoid transplantation in a rat model of middle cerebral artery occlusion (MCAO) found that cerebral infarct volume was greatly reduced and neuromotor function was improved [23]. The transplanted brain organoids imitated cortical development and supported motor-cortex-specific reconstruction.…”
Section: Cell Therapy For Stroke Recoverymentioning
confidence: 99%